Lure, retain, and catch malaria mosquitoes. How heat and humidity improve odour-baited trap performance - Antoine Cribellier; Jeroen Spitzen; Henry Fairbairn; Cedric van de Geer; Johan L. van Leeuwen; Florian T. Muijres (Malaria Journal, 2020)
Abstract Background When seeking a human for a blood meal, mosquitoes use several cues to detect and find their hosts. From this knowledge, counter-flow odour-baited traps have been developed that use a combination of CO2, human-mimicking odour, visual cues and circulating airflow to attract and capture mosquitoes. Initially developed for monitoring, these traps are now also being considered as promising vector control tools. The traps are attractive to host-seeking mosquitoes, but their capture efficiency is low. It has been hypothesized that the lack of short-range host cues, such as heat and increased local humidity, often prevent mosquitoes from getting close enough to get caught; this lack might even trigger avoidance manoeuvres near the capture region. Methods This study investigated how close-range host cues affect the flight behaviour of Anopheles female malaria mosquitoes around odour-baited traps, and how this affects trap capture performance. For this, a novel counter-flow odour-baited trap was developed, the M-Tego. In addition to the usual CO2 and odour-blend, this trap can provide the short-range host cues, heat and humidity. Systematically adding or removing these two cues tested how this affected the trap capture percentages and flight behaviour. First, capture percentages of the M-Tego with and without short-range host cues to the BG-Suna trap were compared, in both laboratory and semi-field testing. Then, machine-vision techniques were used to track the three-dimensional flight movements of mosquitoes around the M-Tego. Results With heat and humidity present, the M-Tego captured significantly more mosquitoes as capture percentages almost doubled. Comparing the flight behaviour around the M-Tego with variable close-range host cues showed that when these cues were present, flying mosquitoes were more attracted to the trap and spent more time there. In addition, the M-Tego was found to have a better capture mechanism than the BG-Suna, most likely because it does not elicit previously observed upward avoiding manoeuvres. Conclusions Results suggest that adding heat and humidity to an odour-baited trap lures more mosquitoes close to the trap and retains them there longer, resulting in higher capture performance. These findings support the development of control tools for fighting mosquito-borne diseases such as malaria.